TRICHOPTERA FAUNA OF THE PALMAR RIVER, CUNDINAMARCA, COLOMBIA - González-Vargas, Geraldine (2021)
The behavioral variation of diversity in different altitudinal scales is one of the variables that have been least studied in aquatic insects, therefore, the objective of this research was to establish how the composition varies of the Trichoptera order present in the Palmar river, Cundinamarca, Colombia with regarding the altitudinal gradient, determining the particular physicochemical conditions that are distributed from its source to its mouth, during the months of September 2018 to February 2019, the capture of individuals was carried out using a Surber network and a type D network, the physicochemical parameters were measured in situ. 3,838 specimens belonging to 10 families and 18 genera were collected, of which the first report of the Anchitrichia (Flint, 1970), Cerasmatrichia (Flint et al., 1994) and Neotrichia (Morton, 1905) genera of the Hydroptilidae family for Cundinamarca is made. The tricopterofauna in the evaluated areas showed a variation at a spatial level, exhibiting the highest richness and abundance in the Ubaque area. The genera Atopsyche (Banks, 1905), Helicopsyche (Siebold, 1856) and Smicridea (McLachlan, 1871) presented the highest distribution ranges as they were present in all areas. The canonical correspondence analysis carried out showed that pH and temperature are the variables that have the greatest weight in the distribution of larvae.